Corporate Parenting Strategies and Performance: A Conceptual Review - Adim , Chidiebere; Emumena, David (Journal of Strategic Management, 2023)
Purpose: The success and performance of corporate entities heavily depend on the strategies adopted by their parent companies. This conceptual review aims to explore the relationship between corporate parenting strategies and organizational performance. Through a comprehensive analysis of existing literature, this review identifies and examines the key components of corporate parenting strategies that influence performance outcomes. The dimensions of corporate parenting are stand-alone influence, linkage influence, central functions and activities and corporate development influence. Performance is measured in terms of sales growth, product quality and innovativeness. Methodology: A desk research methodology is employed in reviewing extant literature on the conceptualized variables. Finding: From the review of literature, it is concluded that corporate parenting influences performance of subsidiaries. Recommendation: The paper recommends that an empirical study should be carried out using various variables in the conceptual model developed so as to test the validity of the concepts reviewed in this paper.